Application of the Analytical Hierarchy Process for Autonomous Truck Strategies of Commercial Vehicles - Ahmad Mohamed; Scott Stone; Amr A. Oloufa (Applied Sciences)
This research reports on the development of a model to measure the value of a given traffic strategy for freight truck traffic through the perspective of multiple involved agencies. The model was designed as an Analytical Hierarchy Process (AHP) model, wherein each perspective was broken down into sub-criteria in subsequent tiers. These sub-criteria would then be compared to each other to determine the overall weights of each perspective in evaluating different traffic control strategies. The model was created to determine the value of four specific perspectives: the Economic, Safety, Environmental, and Mobility Perspectives of a given traffic control strategy. These perspectives were tested through the surveying of 24 experts within the state of Florida involved in the field of transportation, who were consulted to determine the weights of each perspective and its criteria using pairwise comparisons. Once completed, the model was then tested to evaluate the overall priority of three alternatives: one in which no strategy was employed, one in which a strategy was employed at a speed of 55 mph, and one in which it was employed at 75 mph. The results showed that safety was selected as the most important perspective among all the consulted experts. Since the strategy of implementation at 55 mph was deemed the safest, it was calculated as the most sustainable alternative, despite its lower speed and efficiency lowering the economic and mobility priorities. This supports the implementation of the AHP model in upper-level decision making, as it allows management to determine the best decision that will placate all lower-level parties, preventing conflict and increasing overall workplace efficiency.